Natives, the Foreign-Born and High School Equivalents: New Evidence on the Returns to the GED - Melissa A. Clark; David A. Jaeger (Institute for the Study of Labor (IZA), 2002)
In this paper we explore the labor market returns to the General Education Development exam, or GED. Using new data from the Current Population Survey, we examine how the return to the GED varies between U.S. natives and the foreign-born. We find that foreignborn men who hold a GED but received all of their formal schooling outside of the U.S. earn significantly more than either foreign-schooled dropouts or individuals with a foreign high school diploma. For foreign-born men with some U.S. schooling, earning a GED brings higher wages than a traditional U.S. high school diploma, although this difference is not statistically significantly different from zero. These patterns stand in contrast to those for U.S. natives, among whom GED recipients earn less than high school graduates but significantly more than dropouts. The effects for natives appear to become larger over the life cycle and do not seem to be due to cohort effects. While it is difficult to attach a purely causal interpretation to our findings, they do indicate that the GED may be more valuable in the labor market than some previous research suggests.
Keywords: J31; I2; J61; 330; GED; immigration; sheepskin effects; Bildungsertrag; Absolventen; Allgemeinbildende Schule; Migranten; Vereinigte Staaten